Wastewater pollution and quality indicators in the ‘Junín Lake’ National Reserve, Peru - Cusiche Pérez, Leoncio Filiberto; Miranda Zambrano, Gloria Amparo (Revista Mexicana de Ciencias Agrícolas, 2019)
In Peru, water pollution is one of the biggest environmental problems (Custodio and Chávez, 2017), considering that the fragility of aquatic ecosystems destructively impacts biodiversity, whose local biota concentrates unique ecological communities. This problem was studied in Junín Lake, where anthropogenic pressure ignores the conservation and sustainability of the environment and biodiversity. Premium the satisfaction of productive needs (livestock, agriculture and extractive) and the pressure of companies and institutions (mining, hospitals, markets) who pour their wastewater into the lake affecting habitats. The objective of this research was to scrutinize the impact of wastewater on these ecosystems and their area of influence, indicating the level of water quality. The type of research that covered from 2015 to 2017 is descriptive, of longitudinal contemporary evolutionary design. Two sampling periods (rain and drainage) were established for the physicochemical and bacteriological analysis of water. The results show that the biochemical oxygen demand (DBO5) exceeds the maximum permissible limits and during the dry season they are poor quality waters. The wastewater discharges is a polluting factor with danger of toxicity to the aquatic life of the lake, affecting species of endemic flora and fauna and in general the entire ecosystem.